Congenital syphilis - Re-emergence of a much forgotten entity? - Rutva Amlani; Savita Agrawal; Ram Gulati; Kishor Singh; Sonal Jain (Wolters Kluwer Medknow Publications, 2021)
Congenital syphilis is a severe, disabling infection that occurs due to transmission of Treponema pallidum across the placenta. An increase in the incidence of congenital syphilis has been observed in developing countries. Here, we are reporting a case of early congenital syphilis who presented with desquamating papulosquamous lesions over multiple body parts along with moist erythematous and erosive lesions in the perianal and perioral regions. Reactive venereal disease research laboratory and T. pallidum hemagglutination assay test in child and parents confirmed the diagnosis of congenital syphilis.